Survey watch: Actionable research to inform rehabilitation and rebuilding of livelihoods in conflict affected communities in Ethiopia - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
The recent conflicts in Ethiopia have caused massive displacements, loss of lives and livelihoods. Identifying efficient and cost-effective investments to rebuild and sustainably rebuild livelihoods quickly is one immediate and crucial step. The overall objective of the project is to conduct actionable research to inform the rehabilitation and rebuilding efforts in Ethiopia.